Critique and Analysis of the Book Results of Contemporary Arabic Poetry - Seyyed Fazlolah Mirghaderi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Due to the time frame of the so-called contemporary period, the production of abundant poetry and the presence of poets in Arab countries and Arab poets in other countries of the world, it is very difficult to approach contemporary poetry in the form of a book and the template of the thoughts of a research author. Based on his views, contemporary scholar and critic Hassan Ebas has presented some of the approaches of contemporary poetry in the form of a book and has analyzed and criticized those approaches and tried to present most of his critical views in those analyzes. Mention some. In-depth reading of these approaches raises questions such as: Why did the author present these five approaches, and why did each of them have a uniform analysis, and the following sub-headings were not categorized? Undoubtedly, today, the design of contemporary Arabic poetry approaches, considering its breadth, requires a new effort with a new style so that contemporary poetry can be criticized from different dimensions.